JANUSZ REYKOWSKI'S CONCEPT OF MORAL DEVELOPMENT AS AN MULTI-DIMENSIONAL PHENOMENON AND ITS APPLICATIONS IN INTERCULTURAL STUDIES - Ewa Ogrodzka-Mazur (Borys Grinchenko Kyiv Metropolitan University, 2018)
In the present work, an attempt to specify the theory-cognitive signifi cance of Reykowski's concept of multidimensional moral development for intercultural studies. This proposal seems to be particularly useful in pedagogical analyses dealing with moral reasoning of children. The presented research results and their interpretation confi rm the presence of intercultural diff erentiation in the development of evaluation standards of learners in late childhood. Thus, this concept may have broader application in intercultural studies in education.